محددات الإيرادات العامة الفلسطينية وتحليلها - مصطفى أبو مدللة, سمير (مجلة الاقتصاديات المالية البنكية وإدارة الأعمال; No 07 (2018): مجلة الاقتصاديات المالية البنكية و إدارة الأعمال-ديسمبر, 2019)
هدفت الدراسة إلى التعرف على واقع وتطور الإيرادات العامة الفلسطينية في الفترة (1994-2016)، ودراسة أهم المحددات الداخلية والخارجية المؤثرة على الإيرادات، وذلك من خلال استخدام المنهج التحليلي الوصفي حيث قام الباحثان باستعراض واقع الإيرادات العامة (1994-2016)، والوقوف على أهم المحددات الداخلية والخارجية المؤثرة عليها، من خلال محاولة تتبع آثارها على حجم الإيرادات . توصلت الدراسة إلى العديد من النتائج الوصفية وكان أهمها تعدد القوانين الضريبية التي تنظم عملية فرض وجباية الضرائب في فلسطين، وتعدد الإدارات الضريبية والضرائب التي يدفعها المكلفون، ومعاناة الدوائر الضريبية من نقص الموارد البشرية والإمكانيات المادية والتجهيزات الفنية، وغياب التنسيق فيما بينها في العمل، وبينها وبين المؤسسات الحكومية الأخرى، جميعها بالإضافة إلى ضعف تطبيق العقوبات التي يتبناها القانون كل ذلك أدى إلى اتساع ظاهرة التهرب الضريبي، كما يعتبر الاحتلال الإسرائيلي المحدد الأهم لإيرادات السلطة الفلسطينية لسيطرته على المعابر والحدود وتحكمه بالتجارة الخارجية الفلسطينية وبمنطقة ج، وما يسببه من تسرب مالي ناجم عن إيرادات المقاصة وتسربات أخرى منها رسوم معبر الكرامة والمخالفات المرورية للمواطنين الفلسطينيين، وتم بناء استراتيجية على عدة فرضيات تخص الوضع الاقتصادي والسياسي والتسرب المالي، بالإضافة إلى المكلفين المسجلين غير الملتزمين وغير المسجلين . انتهت الدراسة بوضع العديد من التوصيات ذات العلاقة بالمهام التي يجب على السلطة والمجتمع الدولي القيام بها لنجاح لزيادة الايرادات العامة. The study aimed to recognize the reality and the development of the Palestinian public revenues in the period (1994-2016), and studying the most important internal and external determinants  that affecting revenues,  through the use of analytical descriptive approach , as well as studying and analyzing  the reality of the Palestinian public revenues and to show the divisions, and stand on the most important internal and external determinants affecting them. This is done by trying to follow their effects on the size of the revenues. The study reached to  many descriptive results and the most important of them were  the multiplicity of tax laws the  organizing  the imposition and collection of taxes in Palestine, and the multiplicity of tax administrations and the taxes paid by holders, and the suffering of the tax departments of the lack of human resources and material capabilities and technical equipment, and a lack of coordination among them at work, and between them and other government institutions.  In addition to the weakness of the application of the sanctions adopted by all of this law. This  led to the widening of tax evasion phenomenon. The Israeli occupation  is considered the most  important factor to  revenues of the Palestinian Authority، because of controlling   of the borders and  crossings, and governed by the Palestinian foreign trade and zone c. This  caused  financial leak resulting from revenues clearing and other leaks such as, Al-karama crossing  and traffic violations of Palestinian citizens. A strategy has been built on several hypotheses  concerning the economic and political situation and financial leakage, in addition to registered taxpayers who are not committed and are not registered The study concluded that putting several recommendations related  to the tasks that  the Palestinian Authority and the international community must do to increase   public revenue . Key words: Palestinian Authority, public revenues, internal determinants, external determinants.